2002
DOI: 10.1007/s00401-002-0534-8
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic infantile astrocytoma and ganglioglioma: a search for genomic characteristics

Abstract: In the present study the clinical data, histology, proliferation rate, DNA ploidy status and the results of TP53 mutation analysis and comparative genomic hybridization (CGH) of three typical cases of desmoplastic infantile astrocytoma and ganglioglioma are presented. Postoperative disease-free intervals of 11, 8 and 3 years were recorded and in none of the cases were radiological signs of tumor recurrence. No TP53 mutations (exons 5-8) were found. CGH analysis revealed loss of 8p22-pter in one case, while in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…Cytogenetic analysis has been carried out in only four cases 12–15 . All demonstrated a normal karyotype and/or non‐clonal aberrations affecting chromosomes 5q, 9p, 11q, 14q, 17p and 22q.…”
supporting
confidence: 82%
“…Cytogenetic analysis has been carried out in only four cases 12–15 . All demonstrated a normal karyotype and/or non‐clonal aberrations affecting chromosomes 5q, 9p, 11q, 14q, 17p and 22q.…”
supporting
confidence: 82%
“…Classic cytogenetic studies have been performed in a limited number of cases. The only 3 cases studied with comparative genomic hybridization did not show consistent gains or losses (3,16). Molecular studies of DIA revealed no loss of heterozygosity on chromosome 10 or 17 (3,13).…”
Section: Discussionmentioning
confidence: 92%
“…However, the MIB‐1 (mind bomb homolog‐1 (drosophila)) labeling index in the undifferentiated areas has been found to be low (0.5–1.5%) 17 . A few studies on the molecular genetics of DIGs have shown breakpoints on several chromosomes, 18 losses on 8p, and gains on 13q by comparative genomic hybridization techniques 19 …”
Section: Discussionmentioning
confidence: 99%